Literature Review: The Impact of Core Tax System Modernization on the Efficiency of Tax Administration in Indonesia - Irvira Permata; Mohamad Sadikin; Agoestina Mappadang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Core Tax System (CTS) modernization is a strategic initiative undertaken by the Directorate General of Taxes (DGT) to enhance the efficiency and effectiveness of tax administration in Indonesia. This digital transformation aims to improve data integration, strengthen supervisory mechanisms, increase taxpayer compliance, and reduce administrative costs. The study purpose was to analyze the impact of Core Tax System (CTS) modernization on the efficiency of tax administration in Indonesia, with a particular focus on service delivery, supervisory mechanisms, and the quality of tax data. This study also aims to identify the opportunities and challenges arising from the implementation of CTS within the Directorate General of Taxes (DGT). Materials and methods. This research employs a literature review approach by analyzing academic journal articles with emphasis on 2024–2025 and supporting foundational references from earlier years, official policy documents issued by the Directorate General of Taxes, and relevant government publications. The selected literature was reviewed systematically to identify key findings related to the implementation and outcomes of CTS modernization. The findings indicate that the implementation of CTS has contributed positively to tax administration efficiency. Key improvements include faster administrative processes, enhanced data accuracy and validity, and increased automation in monitoring and compliance enforcement. CTS also supports better integration of taxpayer information, which facilitates more effective supervision and risk-based audits. However, several challenges persist, including limitations in technological infrastructure, disparities in human resource readiness, and the need for stronger system integration with other government agencies.Conclusions. Overall, CTS modernization has significant potential to improve tax administration efficiency and reduce the tax gap in Indonesia. Its successful implementation depends on continuous policy support, investment in technological capacity, and ongoing development of human resources to ensure system sustainability and optimal performance.